Improving utilization of nests and decreasing mislaid eggs with narrow width of group nests - Zheng, Hongya; Li, Baoming; Chen, Gang; Wang, Chaoyuan (International Journal of Agricultural and Biological Engineering, 2018)
Provision of nest boxes is necessary for laying hens, especially in non-cage systems. This study investigated the effects of nest width on nest utilization and mislaid eggs. Hy-Line Browns hens were transferred from conventional cages to perchery pens at 12 weeks of age. Two experiments were conducted to mutually verify the hypothesis that narrowing group nests would improve nest utilization and reduce mislaid eggs. In experiment 1, group nests of 150 cm wide in two pens were partitioned at intervals of 50 cm and 37 cm, respectively. In experiment 2, partition panels were removed after acclimation. The number of mislaid eggs and nest eggs in each pre-set section were compared. Results indicated that narrowing group nests had positive effects on improving usage uniformity and efficiency of group nests. Nest eggs were more evenly distributed on the egg belt in both narrowed group nests, which was indicated by the significant decrease of variance among different sections. The proportion of mislaid eggs decreased by 3.5% in 37 cm treatment and 4.7% in 50 cm treatment, respectively. As expected, reuse of the 150 cm group nests after removal of partition panels lowered the usage uniformity of group nests. A growth of three percentage points was found for the proportion of mislaid eggs after removing the partition panels in 50 cm treatment. The present results indicated that it is the width of the nest box that works for a better use of group nests. In conclusion, adding partition panels at intervals of 50 cm and 37 cm in group nests both are effective on nest usage and decreasing the occurrence of mislaid eggs. Keywords: group nest, nest width, utilization, mislaid eggs, hen house, non-cage system, bird welfare DOI: 10.25165/j.ijabe.20181101.3167 Citation: Zheng H Y, Li B M, Chen G, Wang C Y. Improving utilization of nests and decreasing mislaid eggs with narrow width of group nests. Int J Agric & Biol Eng, 2018; 11(1): 83–87.